Exploring the Benefits and Challenges of Mobile Technology in Ghanaian Small-Scale Enterprises - Owusu, Frank; Novignon, Jacob (Journal of Policy Options, 2021)
This study explored the use of mobile technology among entrepreneurs and managers of micro and small-scale businesses in the Akuapem North district of Ghana. The key findings revealed that many entrepreneurs and business managers utilized more than one mobile phone or subscribed to multiple network providers. This behavior was driven by several factors, including the desire to make more affordable calls, access better service quality from various network providers, enhance business operations, ensure security, and manage their extensive contact lists effectively. These insights highlight the significant role of mobile technology in the business strategies of small-scale enterprises in the region. In addition to marketing and sales purposes, the managers and entrepreneurs in the study used mobile phones for a variety of other business-related activities. These included gathering information, managing product delivery and procurement, and handling internal affairs. A Chi-square test further confirmed that mobile phone usage had a positive impact on their businesses, helping to improve customer service, enhance communication with suppliers and customers, facilitate the opening of new branches, stay competitive, and ultimately increase profits. However, despite these benefits, respondents also identified several occasional challenges associated with mobile phone usage. These included issues such as poor reception, sound distortion or calls breaking up, and calls ending unexpectedly. These challenges highlight some of the limitations in the mobile infrastructure that can affect the efficiency of business operations.